2018
DOI: 10.1111/crj.12759
|View full text |Cite
|
Sign up to set email alerts
|

Serum but not exhaled breath condensate periostin level is increased in competitive athletes

Abstract: Increased serum, but not EBC, periostin levels in competitive athletes are probably because of permanently increased exercise load leading to stimulation, injury and regeneration of musculoskeletal tissues. Periostin may be considered marker of long-term exercise overload after confirmation in larger groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In concordance with our results, recent studies showed that serum periostin measurement may be inadequate in differentiating asthmatic and healthy subjects (14,16,25). Serum periostin levels were reported to be higher even in professional athletes compared to asthmatic patients (26).…”
Section: Discussionsupporting
confidence: 90%
“…In concordance with our results, recent studies showed that serum periostin measurement may be inadequate in differentiating asthmatic and healthy subjects (14,16,25). Serum periostin levels were reported to be higher even in professional athletes compared to asthmatic patients (26).…”
Section: Discussionsupporting
confidence: 90%
“…In parallel , a Portuguese study in kayakers revealed lower plasma IL-1β, IL-18, IFN-γ and IL-1ra levels off-training season as compared to training season, which speaks in favor of beneficial anti-inflammatory effect of regular albeit intensive exercise (17). In a small study, significantly higher resting serum levels of periostin in elite swimmers compared to asthmatics or healthy subjects were described (13).…”
Section: Exercise and Systemic Inflammationmentioning
confidence: 93%
“…A single bout of intensive exercise training is associated with the increased synthesis and release of pro‐inflammatory cytokines, with increased serum levels of anti‐inflammatory cytokines (e.g., IL‐10 and IL‐1ra) being observed as a secondary phenomenon 2,12,15–17 . Serum levels of periostin, a hallmark of type 2 inflammation, were not increased within 1 h after acute exercise 18 . In a study assessing serum cytokine responses to treadmill running exercise, resting levels of anti‐inflammatory and immunomodulatory cytokines (IL‐1ra, IL‐10) were higher in URTI symptom‐free subjects 12 .…”
Section: Infection‐like Syndromes In Athletes—when No Pathogen Can Be...mentioning
confidence: 98%
“…Apart from investigations at the systemic level, the potential influence of exercise on inflammation in the upper and lower airways has been studied using non‐ or semi‐invasive airway samplings such as nasal lavage fluid (NLF) and exhaled breath condensate (EBC) 18,30–37 . However, the data acquired so far are inconclusive, partly due to considerable differences in sampling methodology.…”
Section: Infection‐like Syndromes In Athletes—when No Pathogen Can Be...mentioning
confidence: 99%